70.4: A 2.78‐in 1058‐ppi Ultra‐High‐Resolution OLED Display using CAAC‐OS FETs. Issue 1 (June 2015) - Yokoyama, Kohei; Hirasa, Shinichi; Miyairi, Noriko; Jimbo, Yasuhiro; Toyotaka, Kouhei; Kaneyasu, Makoto; Miyake, Hiroyuki; Hirakata, Yoshiharu; Yamazaki, Shunpei; Nakada, Masataka; Sato, Takahiro; Goto, Naoto
Abstract : Using a WTC OLED device and a backplane using CAAC‐OS FETs over a glass substrate employing the 1.5 µm rule, we fabricated a 2.78‐in 1058‐ppi OLED display, the pixel density of which is the highest in the world among displays using thin film transistors over a glass substrate.